Subacute sclerosing pan encephalitis with different perspective: an atypical case - Goyal, Anant; Kumari, Neha; Ahmad, Muneer (International Journal of Contemporary Pediatrics, 2025)
Subacute sclerosing pan encephalitis (SSPE) is a rare type of brain disease that happens when a changed version of the measles virus keeps infecting the brain. The symptoms start with changes in behavior, then seizures, trouble thinking, stiff muscles, and eventually, the person might go into a coma and die. A 7-year-old male patient presented in OPD with complaint of single episode of generalized tonic clonic seizures lasting for 30 seconds, followed by left sided upper limb and lower limb weakness along with myoclonic seizures. Patient was active and on walking patient was swaying towards right side. Supportive management with anti-epileptics given but patient has poor prognosis. Our case showed three unusual signs of SSPE: starting at a young age, sudden loss of balance showing a fast disease progress, and happening in a child who had been vaccinated but didn’t have a known measles infection. We think the child might have had a mild measles infection that wasn’t noticed by the parents, which could have led to SSPE.